2018
DOI: 10.1021/acsanm.8b00192
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Quality Criteria of Citrate-Protected Gold Nanoparticles for Medicinal Applications

Abstract: Gold nanoparticles (GNPs) are one of the most widely studied and utilized materials in nanomedicine, but there is no business or national quality standard for their medicinal applications. This has become the bottleneck in the translation of clinical applications of gold-based nanomaterials. To solve this issue, the most frequently used citrate-reduced GNPs were selected as demonstration in this study to conduct quality standard research. The different molar ratios of chloroauric acid to trisodium citrate in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…MTX peaks around 280 and 308 nm also remained unaltered, confirming the stability of the synthetized conjugates. This is in accordance with the results obtained in other studies [ 24 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…MTX peaks around 280 and 308 nm also remained unaltered, confirming the stability of the synthetized conjugates. This is in accordance with the results obtained in other studies [ 24 ].…”
Section: Resultssupporting
confidence: 94%
“…HAuCl 4 presented a peak around 300 nm which disappeared, with a new peak emerging at 519 nm corresponding with the surface resonance plasmon band (SPR) of AuNPs [ 9 , 10 , 12 , 23 ]. Figure 1 b shows a bathochromic shift around 525 nm for the AuNP–MTX conjugates, which indicates an increase in size particle [ 24 ] and also a modification in the nanoparticle’s surface [ 25 ]. This could be due to the chemical absorption of MTX into the AuNP’s surface, justifying the band shift from 519 to 525 nm [ 8 , 9 , 10 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…MTX peaks around 280 and 308 nm also remained unaltered, confirming the stability of the synthetized conjugates. This is in accordance with the results obtained in other studies [27]. Short term study confirmed that they were not stable when diluted by only phosphate buffered solution (PBS), while in the presence of fetal bovine serum (FBS) the particles are stable at least for 24 h without the addition of DMEM.…”
Section: Stability Analysis Of Aunps-mtx Conjugatessupporting
confidence: 91%
“…HAuCl4 present a peak around 300 nm which disappeared emerging a new peak at 519 nm corresponding with the surface resonance plasmon band (SPR) of AuNPs [9,10,12,26]. Figure 1b shows a bathochromic shift around 525 nm for the AuNPs-MTX conjugates, which indicates an increase in size particle [27] and also a modification in the nanoparticles surface [28]. This could be due to the chemical absorption of MTX into the AuNPs surface, justifying the band shift from 519 to 525 nm [8][9][10]12].…”
Section: Characterization Of Aunps and Aunps-mtx 211 Uv-vis Spectrmentioning
confidence: 95%
“…Citrate-GNPs of 56, 33, and 15 nm regulated the proportion of HepG2 cells in the G2/M phase, with 15 nm citrate-GNPs inducing the highest level of G2/M cell-cycle arrest [135]. ZnO NPs of 20 nm enhanced the proportion of HeLa cells in the G2/M phase, while ZnO NPs of 40 nm and 80 nm did not induce G2/M arrest [136].…”
Section: The Impact Of Np Size On Cell-cycle Arrestmentioning
confidence: 96%